Flowmotion Monitored by Flow Mediated Skin Fluorescence (FMSF): A Tool for Characterization of Microcirculatory Status - Katarzynska, Joanna; Cholewinski, Tomasz; Sieron, Leslaw; Marcinek, Andrzej; Gebicki, Jerzy (Frontiers in Physiology, 2020)
Oscillations in the microcirculation, known as flowmotion, are a well-recognized characteristic of cutaneous blood flow. Since flowmotion reflects the microcirculatory status of the vascular system, which is very often impaired in many diseases and disorders, a quantitative assessment of skin flowmotion could potentially be used to screen for early symptoms of such conditions. In this study, skin flowmotion was monitored using the Flow Mediated Skin Fluorescence (FMSF) technique. The flowmotion parameter was defined for quantitative assessment of basal flowmotion at rest (FM) and during reperfusion followed the post-occlusive reactive hyperemia (FM(R)). The study population involved healthy volunteers between the ages of 30 and 72 (n = 75). The FM parameter showed an inverse dependence relative to age and the FM(R) parameter was inversely correlated to blood pressure. The FM(R) parameter reflects the strong effect of hypoxia on flowmotion, which is mainly due to the increased myogenic activity of the vessels. The FMSF technique appears to be uniquely suited for the analysis of basal flowmotion and its hypoxia response and may be used for characterization of microcirculatory status.